Cycling on rollers: Kreitler Fan Resistance at submaximal levels of effort - Reiser, R. F.; Hart, C. R. (International Journal of Sports Medicine, 2008)
The goal of this investigation was to characterize the commercially available fan unit for the Kreitler® Alloy rollers at submaximal levels of effort (= 500 W). A single cyclist rode six times at each of three fan inlet settings (closed, half, and full open) and five fan speeds (900, 1800, 2700, 3600, and 4500 rpm). Fan power requirements were isolated by subtracting roller resistance from separate trials. Power requirements relative to fan inlet and fan speed possessed a significant interaction with the main effects for each also significant (all p < 0.001). Power increased to the cube of fan speed, regardless of inlet opening (r2 = 0.997). Fan resistance was virtually non existent at 900 rpm. Fan resistance then significantly increased with increasing fan speed and inlet opening. At 4500 rpm power requirements of the fan reached 269 ± 6, 352 ± 7, and 406 ± 9 W with the inlet closed, half, and fully open, respectively (p < 0.001). The rear wheel-roller interaction supplied an additional 19 ± 2 W on up to 104 ± 4 W at the highest speed. Therefore, the fan unit increases the functionality of the rollers for a variety of training and testing environments.